Integration of photosynthesis, development and stress as an opportunity for plant biology. Issue 3 (14th July 2015) - Allahverdiyeva, Yagut; Battchikova, Natalia; Brosché, Mikael; Fujii, Hiroaki; Kangasjärvi, Saijaliisa; Mulo, Paula; Mähönen, Ari Pekka; Nieminen, Kaisa; Overmyer, Kirk; Salojärvi, Jarkko; Wrzaczek, Michael
Summary: With the tremendous progress of the past decades, molecular plant science is becoming more unified than ever. We now have the exciting opportunity to further connect subdisciplines and understand plants as whole organisms, as will be required to efficiently utilize them in natural and agricultural systems to meet human needs. The subfields of photosynthesis, plant developmental biology and plant stress are used as examples to discuss how plant science can become better integrated. The challenges, strategies and rich opportunities for the integration of the plant sciences are discussed. In recent years, more and more overlap between various subdisciplines has been inadvertently discovered including tradeoffs that may occur in plants engineered for biotechnological applications. Already important, bioinformatics and computational modelling will become even more central to structuring and understanding the ever growing amounts of data. The process of integrating and overlapping fields in plant biology research is advancing, but plant science will benefit from dedicating more effort and urgency to reach across its boundaries.